Endoscopic Self-Expanding Metal Stents for Acute Colonic Obstruction. Issue 1 (January 2013) - Tirosh, Dan; Perry, Zvi; Walfisch, Shlomo; Rozental, Alex; Fich, Alex; Krugliak, Pavel; Mizrahi, Solly; Kirshtein, Boris
The current study presents our experience with the introduction of self-expanding metal stents (SEMS) and assesses success rate, clinical outcomes, and complications. We conducted a historical cohort study reviewing endoscopic SEMS insertions between 2000 and 2010. Overall, 51 patients underwent stent insertion: 38 with an emergent procedure and 13 with a semielective procedure. SEMS was inserted in 27 men and 24 women with a mean age of 68.9 years. Colonic malignancy was the cause of obstruction in all patients. The tumors were localized in the rectosigmoid in 33 (64.7%), in the left colon in 16 (31.4%), and in the right colon in two cases (3.9%). Endoscopic SEMS insertion was technically successful in 68.4 per cent of patients in an emergency and in 84.6 per cent of patients in a semielective setting. Successful stent insertion allowed a "bridge to surgery" in 23 and palliative care in 14 patients. Stent migration occurred in three, obstruction in two, and bowel perforation in three cases. Nineteen patients in the emergent group underwent a subsequent successful semielective colonic resection within 8.1 days (range, 2 to 30 days) of stent insertion. There were two cases (11.1%) of major and four cases (22.2%) of minor postoperative complications in this series. No anastomotic leaks were observed. Mean postoperative hospitalization was 10.1 days (range, 5 to 45 days). Endoscopic stent insertion is a relatively simple procedure providing an effective first-line treatment for relief of symptoms of acute malignant colorectal obstruction, preventing acute perforation, and serving either as a preoperative procedure (allowing lower morbidity semielective surgery) or as palliative care.